VALIDATION OF THE PERCEICED MOTIVES FOR PHYSICAL ACTIVITY MEASURE IN SPANISH PRACTITIONERS: DIFFERENCES FOR PARTICIPATION REASONS - Moreno Murcia, Juan Antonio; Cervelló Gimeno, Eduardo; Martínez Camacho, Antonio (Anales de Psicología / Annals of Psychology, 2007)
The aim of the study is the validation of the Spanish context from the MPAM-R scale (Motives for Physical Activity Measures revised), by Ryan, Fredericks, Lepes, Rubio and Sheldon(1997), and check the effects that produce in the kind, age, form, time and days for practice in that reasons. It has been used a sample composed of 561 adults subjects from a big Spanish city with practice do non – competitive sport and physical activities. It was a made a factorial explore analysis obtaining an adaptation of the original scale with 28 items grouped in five factors with good reliability coefficients and a total variance explained of 69.36%.The reasons that are link with the health gives medium securities highest with relation with the enjoy and funny. People with old age give more importance to the reasons that are link with health while young people consider more importance the reasons that are link with health while young people consider more importance the reasons that are link whit the appearance. With regard to the kind, the study gives that women practice for reasons of health, appearance, social and enjoy, the same as men. It is consider that the MPAM-R scale can be a valid and reliable instrument for measure the reasons for practice physical activity and it is precised news works in the field of the non-competitive physical activity.